Associations between squalene epoxidase gene polymorphisms and obesity - Jia-Qing Yu; Feng-Xia Wang; Shuai Liu; Bing Zhu; Yi-Tong Ma (PeerJ)
Background Among the known control points of cholesterol synthesis, squalene epoxidase (SQLE) is considered a key factor influencing cholesterol metabolism. Methods A total of 1,045 consecutive participants were divided into an obese group and a control group. Blood biochemical markers were measured, and deoxyribonucleic acid (DNA) was extracted from all participants. Statistical analyses were conducted to assess the associations between SQLE gene single nucleotide polymorphisms (SNPs) and obesity. Results The C/C genotype of SQLE SNP1 (rs10104486) was significantly more associated with obesity compared to the A/A genotype. A significant difference in genotype distribution frequency for rs10104486 was observed between the obese and control groups. The recessive model (CC vs. AC + AA) also showed a statistically significant difference. For SQLE SNP2 (rs2288312), differences were found in genotype distribution frequency, allele frequency, and the recessive model (GG vs. AA + AG) between the two groups. Conclusions This study indicates a correlation between the SQLE gene polymorphisms rs10104486 and rs2288312 and obesity in a young population. Participants carrying the C allele of rs10104486 were more likely to develop obesity than those carrying the A allele, with the CC genotype identified as a predisposing factor.